Steganography: a review of information security research and development in Muslim world - Yunus, Yunura Azura; Ab Rahman, Salwa; Ibrahim, Jamaludin (AJER, 2013)
Conveying secret information and establishing hidden relationship has been a great interest since long time ago. Therefore, there are a lot of methods that have been widely used since long past. This paper reviewed one of the methods for establishing hidden communication in information security and has gained attraction in recent years that is Steganography. Steganography is the art and science of hiding a secret message in a cover media such as image, text, signals or sound in such a way that no one, except the intended recipient knows the existence of the data. In this paper, the research and development of steganography from three years back starting from 2010 until recently, 2013 in Muslim world are reviewed. The future research in the field of Steganography is briefly discussed.